Ion beam control in laser plasma interaction. (March 2016) - Kawata, S.; Izumiyama, T.; Sato, D.; Nagashima, T.; Takano, M.; Barada, D.; Gu, Y. J.; Ma, Y. Y.; Kong, Q.; Wang, P. X; Wang, W. M.
Abstract: By a two-stage successive acceleration in laser ion acceleration, our 2.5-dimensional particle-in-cell simulations demonstrate a remarkable increase in ion energy by a few hundreds of MeV; the maximum proton energy reaches about 250MeV. The ions are accelerated by the inductive continuous post-acceleration in a laser plasma interaction together with the target normal sheath acceleration and the breakout afterburner mechanism. An intense short-pulse laser generates a strong current by high-energy electrons accelerated, when an intense short- pulse laser illuminates a plasma target. The strong electric current creates a strong magnetic field along the high-energy electron current in the plasma. During the increase phase in the magnetic field strength, the moving longitudinal inductive electric field is induced by the Faraday law, and accelerates the forward-moving ions continously. The multi-stage acceleration provides a unique controllability in the ion energy and its quality.